1983
DOI: 10.1002/1097-4679(198311)39:6<970::aid-jclp2270390626>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Actual and recalled test anxiety and flexibility, rigidity, and self-control

Abstract: Recalled and actual test anxiety were compared, and the interrelationship of anxiety and certain personality variables was examined. Sex differences in the variables and in the correlations among variables were studied. The A‐State scale of the State‐Trait Anxiety Inventory was administered to a sample of college students (N = 71) under different conditions and instructions. Scales that measure trait anxiety, dependency, flexibility, and self‐control also were administered. Recalled test anxiety was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…A number of previous studies have shown that people tend to overestimate the intensity of past negative emotions (Breckler, 1994;Devito & Kubis, 1983;Keuler & Safer, 1998;Schrader et al, 1990;Zimmerman & Coryell, 1986). In the present study, no general tendency was found to either overestimate or underestimate past emotions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A number of previous studies have shown that people tend to overestimate the intensity of past negative emotions (Breckler, 1994;Devito & Kubis, 1983;Keuler & Safer, 1998;Schrader et al, 1990;Zimmerman & Coryell, 1986). In the present study, no general tendency was found to either overestimate or underestimate past emotions.…”
Section: Discussionmentioning
confidence: 94%
“…Although several researchers have found that people tend to overestimate the intensity of past negative emotions (Breckler, 1994;Devito & Kubis, 1983;Keuler & Safer, 1998;Schrader et al, 1990;Zimmerman & Coryell, 1986; but see Levine, 1997;Levine & Bluck, 1997), we predicted that current appraisals would determine whether emotions were over-or underestimated relative to initial reports. To test this prediction, the complete regression models described above were used to estimate values for recalled emotional intensity at selected levels of the current appraisal variables.…”
Section: Overestimates and Underestimates Of Emotional Intensitymentioning
confidence: 96%
See 1 more Smart Citation
“…For example, studies by Schrader et al (1990) and by Zimmerman and Coryell (1986) found that depressed patients significantly overestimated the intensity of previous episodes of depression. Overestimates of past states have also been observed in memory for pre-exam anxiety (Devito & Kubis, 1983;Keuler & Safer, 1998), blood donation anxiety (Breckler, 1994), and physiological states such as chronic pain (Bryant, 1993). Findings such as these have led some researchers to argue that emotions are not…”
mentioning
confidence: 99%
“…Consistent with previous research (e.g. Devito & Kubis, 1983), participants recalled their pre-exam anxiety levels as being higher than they had indicated in their original ratings. The critical manipulation in this study was that half the participants had received their exam results (the informed group) and half had not (the uninformed group).…”
mentioning
confidence: 99%